دور التأجير التمويلي في تمويل المشروعات الصغيرة والمتوسطة - صيام, أحمد زكريا (جامعة الوادي - University of Eloued, 2014)
هدفت الدراسة إلى التعرف على دور التأجير التمويلي في تمويل المشروعات الصغيرة والمتوسطة من وجهة نظر المالكين وذلك بالاعتماد على المنهج الوصفي التحليلي وقد تألف مجتمع الدراسة مـن جميع المشروعات الصغيرة والمتوسطة في محافظة عمان العاصمة وتم اختيار عينة عشوائية قدرها (120) مالكا، وقد استخدمت الدراسة الاستبانة لتحقيق اهداف الدراسة. The study aimed to identify the role of financial leasing in the financing of small and medium enterprises from the point of view of owners, based on descriptive analytical methodology. The study population consisted of all small and medium enterprises in Amman Governorate. A random sample of 120 owners was selected. To achieve the objectives of the study.
مقال
Keywords: التأجير التمويلي، المؤسسات الصغيرة والمتوسطة; Leasing, small and medium enterprises